The impact of corporate social responsibility on consumer brand advocacy: The role of moral emotions, attitudes, and individual differences - Xie, Chunyan; Bagozzi, Richard P.; Grønhaug, Kjell (Journal of business research, 2019)
We investigate the effect of corporate social responsibility (CSR) on consumer advocacy behaviors toward corporate brands. We focus on the mediating roles of positive moral emotions (awe, gratitude, and elevation) and attitudes. The moderating effects of social justice values and empathy on such mediation processes are further explored. A between-subjects field experiment is used to test our hypotheses on a sample of adult consumers. The results show that both positive moral emotions and attitudes mediate the effect of perceived CSR actions on brand advocacy behaviors; however, social justice values and empathy play a different role in regulating the elicitation of moral emotions and attitudes, depending on the type of CSR actions. We add to extant research on CSR and consumer-brand relationships by showing that CSR actions influence brand advocacy of corporate brands and further providing an integrated theoretical framework to explain psychological mechanisms underlying such an effect.